Freely orbiting magnetic tweezers to directly monitor changes in the twist of nucleic acids - Lipfert, Jan (Nat Commun, 2011)
The double-stranded nature of DNA links its replication, transcription and repair to rotational motion and torsional strain. Magnetic tweezers (MT) are a powerful single-molecule technique to apply both forces and torques to individual DNA or RNA molecules. However, conventional MT do not track rotational motion directly and constrain the free rotation of the nucleic acid tether. Here we present freely orbiting MT (FOMT) that allow the measurement of equilibrium fluctuations and changes in the twist of tethered nucleic acid molecules. Using a precisely aligned vertically oriented magnetic field, FOMT enable tracking of the rotation angle from straight forward (x,y)-position tracking and permits the application of calibrated stretching forces, without biasing the tether's free rotation. We utilize FOMT to measure the force-dependent torsional stiffness of DNA from equilibrium rotational fluctuations and to follow the assembly of recombination protein A filaments on DNA.